A study on the global burden of non-melanoma skin cancer from 1990 to 2019 - Zixiang Si; Jieya Ying; Yingli Zhou (Archives of Medical Science)
Introduction This study aimed to provide an overview and analysis of the global disease burden of non-melanoma skin cancer using data from the Global Burden of Disease 2019 (GBD 2019) database.